Sexual Offenses Against Minors (Material and Procedural Aspects) - San Martín Castro, César (2007)
In this paper, the author conducts a study of the various sexual crimes that threaten the sexual indemnity of minors under 18 years of age, taking into account the constituent elements of the crimes, as well as the norms that punish them. The author begins by pointing out that these crimes have undergone a series of changes that have reflected an intense legislative evolution in recent years. To that extent, it is important to analyze these changes and determine the scope of these rules for the justice system. Under this premise, it is relevant to develop the main criminal offenses against minors, such as rape or carnal access, indecent assault, trafficking in persons, child sexual exploitation and pimping. In this context, this article addresses the problems surrounding the rules that deal with these crimes; it also examines the procedural rules, which highlight the importance of protecting the victims because of their special vulnerability.